Experimental study on the static performance of arched aluminium alloy gusset joints. (1st November 2021) - Wu, Jinzhi; Zang, Mengfan; Sun, Guojun; Chen, Song
Highlights: The failure mode of the arched aluminium alloy gusset joint is obtained via test. The static performance of the gusset joint is studied via numerical simulation. The effect of various angle of joints on static property is offered via simulation. Abstract: A gusset joint with 7° arch angle comprised of two upper and lower aluminium alloy joint plates and four H-shaped aluminium alloy members connected by Huck bolts is first designed and the static performance experiment is carried out to address the research gap regarding the static performance of arched aluminium alloy gusset joints. The failure modes of the joint are summarized in terms of the collapse phenomena, namely the local buckling of the web and the bending and torsion failure of the member, and the stress distribution is discussed based on the measured strain. Subsequently, the ultimate bearing capacity and the stiffness in different stages of the load–displacement curve are obtained. The analysis is then developed via finite element (FE) models implemented in the non-linear code ABAQUS. First, via comparison with the experimental results, the validity of the FE model is verified. Furthermore, according to the simulation, it reveals that with the plasticity development of bolt hole walls, the joint gradually reaches the ultimate bearing capacity and undergoes the obvious deformation utill it can not bear the load. To develop further understanding, the effects of different arch angles on the bearing capacity, stiffness, and failure modes of joints are investigated, and the results indicates that arch angles cannot be ignored.